Structural models and endogeneity in corporate finance: The link between managerial ownership and corporate performance - Coles, Jeffrey L.; Lemmon, Michael L.; Felix Meschke, J. (Journal of Financial Economics, 2012)
This paper presents a parsimonious, structural model that isolates primary economic determinants of the level and dispersion of managerial ownership, firm scale, and performance and the empirical associations among them. In particular, variation across firms and through time of estimated productivity parameters for physical assets and managerial input and corresponding variation in optimal compensation contract and firm size combine to deliver the well-known hump-shaped relation between Tobin's Q and managerial ownership. To assess the effectiveness of standard econometric approaches to the endogeneity problem, we apply those remedies to panel data generated from the model. The unfortunate conclusion is that, at least in the ownership–performance context, proxy variables, fixed effects, and instrumental variables do not generally provide reliable solutions to simultaneity bias.